Desire for excellence reflections on Plato and Spinoza - Mutlu, Vicdan. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2004., 2004)
The main aim of this thesis is to provide a good understanding of Plato's and Spinoza's desire for excellence and show in what respects their views resemble and differ from each other. To achieve this aim, their notions of 'desire' and 'excellence' have been examined. Some of the questions that have been raised in this thesis are as following: 'What is the nature of our desires?', 'What is excellence?', 'What is the relation between excellence and goodness?', 'Is excellence something subjective or objective?', 'Does everybody desire only the good?', 'Is desire for excellence a unique privilege of philosophers?', 'Is excellence something attainable for man?', 'Who can approximate to excellence?', 'Does excellence lead to happiness?' 'Is excellence an assimilation to God?'The present study also aims to show the consistencies/inconsistencies of their ideas and the problems in their theses, when necessary, and to come up with a fair interpretation of their work.In this thesis I argue that Spinoza's notion of excellence is deeply connected to 'the Third Kind of Knowledge', on the other hand, Plato's notion of excellence is connected to 'the Knowledge of the Form of the Good'. I also claim that for both philosophers the way to excellence lies in wisdom, that is, in being virtuous and living the life of reason. The ultimate excellence, according to them, is beyond our reach, but they have drawn an ideal model of life to be pursued, although even they were not able to attain that model. The nature of this ideal model of life is the subject matter of this thesis. It is also argued that, for both Plato and Spinoza, desire for excellence is a unique privilege of philosophers. Also approximation to excellence can be achieved only by those people who are living the life of reason, i.e. philosophers like Plato and Spinoza.
Keywords: Excellence.